RESEARCHES REGARDING THE INFLUENCE OF THE NUTRITION SPACE AT CASSIA ANGUSTIFOLIA Vahl. (SENNA) SPECIES CULTIVATED UNDER THE CONDITIONS OF A.R.D.S. SECUIENI - OANA MIRZAN; MARGARETA NAIE; SIMONA-FLORINA ISTICIOAIA; MARIA BOSTAN; BOGDAN MIRZAN (Journal of Engineering Studies and Research)
The present paper presents the results on the influence of the nutrition space at Cassia angustifolia Vahl. (Senna), cultivated under the conditions of A.R.D.S. Secuieni in 2017. The interaction of the studied factors was characterized by very significant negative differences to the production of fresh herb at Cassia angustifolia compared to the control variant (30666 kg/ha) at the distance between rows of 50 cm and 70 cm at all three distances between plants per row (continuous row, 15 cm and 25 cm).